2021
DOI: 10.1097/md.0000000000023979
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Navigation Bronchoscopy Combined Endobronchial Ultrasound in the Diagnosis of Lung Nodules

Abstract: Electromagnetic navigational bronchoscopy (ENB) combined with a radial endobronchial ultrasound probe realizes a combination of magnetic navigation and ultrasound imaging, allowing for the accurate navigation of peripheral lung lesions in real time during surgery. ENB has been evaluated in many studies. However, a comparative report on the feasibility of ENB combined radial endobronchial ultrasound diagnosis in different density lung nodules was small, and few of these studies have reported long-term follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
1
2
0
2
Order By: Relevance
“…When this was combined with EBUS, the diagnostic yield was 92%. This study showed that it is acceptable, safe, and feasible to combine these procedures (6,11,12). Another study showed similar results with diagnostic yields for patients undergoing percutaneous biopsy being 90% and when combined with EMN was 92%; an increase in diagnostic yield by 20% when adding percutaneous needle biopsy has also been shown (17,18).…”
Section: Lung Cancer Diagnosissupporting
confidence: 61%
“…When this was combined with EBUS, the diagnostic yield was 92%. This study showed that it is acceptable, safe, and feasible to combine these procedures (6,11,12). Another study showed similar results with diagnostic yields for patients undergoing percutaneous biopsy being 90% and when combined with EMN was 92%; an increase in diagnostic yield by 20% when adding percutaneous needle biopsy has also been shown (17,18).…”
Section: Lung Cancer Diagnosissupporting
confidence: 61%
“…A prospective randomized controlled trial reported that the combined use of RP-EBUS along with ENB has better diagnostic yield of 88% compared to either technology alone [131]. A single-center retrospective study also demonstrated that ENB combined with RP-EBUS biopsy for the diagnosis of PPLs was safe and effective [132].…”
Section: Ebus+enbmentioning
confidence: 99%
“…Recently, researchers have recognized the fact that ENB requires the support of X-ray fluoroscopy, CBCT or EBUS for adjustment before biopsy to achieve a higher diagnostic rate. 70,[104][105][106][107][108] One-year data from a prospective, multicenter, global cohort study (NAVIGATE study) found that the diagnostic rate of ENB combined with pre-biopsy adjustment can reach 73%. 109 Studies have shown that PPLs with diameter ⩾2 cm and located in the upper lobe or middle lobe are important univariate predictors.…”
Section: Virtual Bronchoscopy Navigationmentioning
confidence: 99%